The Impact of Social Media on Organizational Innovation in Cultural Institutions: A Mediation Analysis of Visitor Co-Creation and Competitive Performance - Radiany, Ade Asria; Mu'min, Halek; Darma; Purnawan, Medi Primatori; Biki, Syamsul B (International Journal of Accounting and Economics Studies, 2025)
This study examines how social media-driven innovation enhances competitive advantage in art galleries and museums, with particular focus on the mediating role of visitor co-creation processes. Using a mixed-methods approach, we collected data from 412 cultural institutions across Indonesia through structured surveys and follow-up interviews. Structural equation modeling (SEM) was employed to test the hypothesized mediation model, with bootstrap analysis for indirect effects. Results demonstrate that social media adoption significantly influences organizational innovation capabilities, which in turn enhances competitive performance. Visitor co-creation fully mediates this relationship, explaining 73% of the total effect. Museums with higher visitor co-creation engagement showed 34% better performance metrics compared to traditional institutions. The cross-sectional design limits causal inferences, suggesting future longitudinal studies should examine the temporal dynamics of digital transformation in cultural sectors. Cultural institution managers should prioritize social media platforms that facilitate visitor co-creation, particularly Instagram, TikTok, and interactive museum apps, as primary drivers of innovation and competitive advantage. This research is the first to empirically demonstrate the mediating mechanism through which social media influences competitive performance in cultural institutions, contributing to both digital innovation and cultural management literature.
Keywords: Social media, organizational innovation, visitor co-creation, competitive advantage, cultural institutions, digital transformation